THE ROLE AND SOCIAL ACTIVITY OF SADRIDDIN AYNI IN THE JADID MOVEMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article describes Sadriddin Ayni's activities in the Jadid movement and Jadid schools at a time of complex socio-political processes, during which the reform and Jadid movements in the emirate changed his worldview and his efforts to develop society.